Walking humbly with the Moros towards the kingdom a reflection on the Catholic Church's mission in Muslim Mindanao - Mendoza, Ruben C. (2012)
In this reflection, I address the question of the Catholic Church's mission in Muslim Mindanao as it responds to the long-standing aspiration of the Moros for self-determination. First, I give an overview of the dialogue between Filipino Christians and Moros, contextualizing this within Philippine history, the changes brought about by Vatican II, and the contemporary challenge of overcoming prejudices. And second, I ask what kind of voice the church must speak if it is to be a credible gospel witness in Bangsamoro. It seems to me that the church needs to be a voice of compasion, justice, and peace in a context that has seen so much violence. In addition, I will suggest that there are two Filipino values, namely pakikipagkapwa-tao and pakikiramay, which are already operative in those who engage in dialogue and peacebuilding efforts, but which need to be foregrounded as cultural resources in responding to the conflict. As ecclesia semper reformanda est, conversion will always be an indispensable element of its journey toward the realization of the Kingdom in Muslim Mindanao.
Keywords: Muslim-Christian relations; Bangsamoro; Catholic Church